Scoping Review: Status Selenium pada Pasien COVID-19 - Malisya Desilian Triningrum; Mirasari Putri; Julia Hartati (Bandung Conference Series: Medical Science, 2022)
Abstract. Selenium (Se) is a micronutrient that plays an important role in the balance of immune function and response. Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is the cause of the COVID-19 pandemic and is the cause of the increasing mortality rate. Selenium deficiency causes oxidative stress and cytokine storms that can affect the severity and mortality risk of COVID-19. This scoping review study aims to determine selenium levels and analyze selenium status in COVID-19 patients. There were 3 databases used, that were PubMed, ScienceDirect, and ProQuest with the keywords selenium AND COVID-19. The number of articles from 2019-2021 were 2,052 articles. Through screening (PRISMA) and critical appraisal (JBI), 6 articles were obtained which were further analyzed. The analysis results on 6 articles found that the occurrence of Se deficiency in COVID-19 patients. Four articles stated that Se deficiency was associated with the severity of COVID-19 and 2 articles stated that Se deficiency was associated with the mortality risk of COVID-19. Meanwhile, one article stated that Se deficiency was not associated with severity and mortality risk however, it remains a risk factor for COVID-19. Selenium has antioxidant, anti-inflammatory, antiviral activity that can reduce oxidative stress that causes tissue damage so as to reduce the severity of COVID-19. In this study, it can be concluded that there is a deficiency Se status in COVID-19 patients. Decreased Se status is related to the severity of COVID-19. Abstrak. Selenium (Se) merupakan mikronutrien yang berperan penting dalam keseimbangan fungsi dan respon imun. Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) merupakan penyebab pandemi COVID-19 dan menjadi penyebab meningkatnya angka kematian. Defisiensi selenium menyebabkan terjadinya stres oksidatif dan badai sitokin yang dapat memengaruhi tingkat keparahan dan risiko mortalitas COVID-19. Studi scoping review ini bertujuan untuk mengetahui kadar selenium dan menganalisis status selenium pada pasien COVID-19. Database yang digunakan ada 3 yaitu PubMed, ScienceDirect, dan ProQuest dengan kata kunci selenium AND COVID-19. Jumlah artikel dari tahun 2019-2021 terdapat 2.052 artikel. Melalui skrining (PRISMA) dan critical appraisal (JBI), didapatkan 6 artikel yang dianalisis lebih lanjut. Hasil analisis pada 6 artikel didapatkan bahwa terjadinya defisiensi Se pada pasien COVID-19. Pada 4 artikel menyatakan defisiensi Se berhubungan dengan tingkat keparahan COVID-19 dan 2 artikel menyatakan defisiensi Se berhubungan dengan risiko mortalitas COVID-19. Sedangkan, satu artikel menyatakan defisiensi Se tidak berhubungan dengan tingkat keparahan dan risiko mortalitas namun, tetap menjadi faktor risiko COVID-19. Selenium memiliki aktivitas sebagai antioksidan, anti-inflamasi, dan antivirus yang dapat menurunkan stres oksidatif yang menyebabkan kerusakan jaringan sehingga dapat mengurangi tingkat keparahan COVID-19. Pada penelitian ini dapat disimpulkan bahwa terjadinya penurunan status Se pada pasien COVID-19. Status Se yang mengalami penurunan berhubungan dengan tingkat keparahan COVID-19.